Self help group is an effective microfinance model for socio-economic empowerment of women: Evaluation from Bodoland Territorial Region in Assam, India - Islam, Md Anowarul; Brahmachary, Pradip (Edelweiss Applied Science and Technology, 2025)
Self-Help Groups (SHGs) have emerged as an effective strategy for women’s empowerment in many South Asian countries. In India, the Self-Help Group Bank Linkage Programme (SBLP) has been a key initiative that connects Self-Help Groups with banks to improve social cohesion, financial inclusion, and income generation. This study considered 280 participants to investigate how SHG participation impacts women’s socio-economic empowerment in the Bodoland Territorial Region (BTR), Assam. We used various statistical tools, such as chi-square, t-tests, regression analysis, and Kruskal-Wallis tests, to analyze the data collected through a structured questionnaire. The results of the study revealed that SHG membership significantly improves women's ability to access health services, participate in group meetings, and manage banking activities. Chi-square tests indicated strong associations between SHG involvement and improvements in household decision-making in some areas, such as children's education, family planning, asset accumulation, and financial management. A paired-samples t-test further confirmed a statistically significant increase in monthly income following SHG membership. Logistic regression results showed that expenditure on food positively influences economic empowerment, whereas spending on clothing and health had an inverse association. Additionally, a Kruskal-Wallis test revealed no significant differences in entrepreneurial traits across educational levels, suggesting that SHGs promote entrepreneurship regardless of formal education. These findings highlighted how SHGs have the potential to be inclusive and transformative in boosting women's economic agency, decision-making authority, and entrepreneurial skills. The study highlighted SHGs as effective platforms for fostering sustainable and equitable empowerment, capable of bridging socio-economic disparities among women in BTR.